2012
DOI: 10.1159/000335185
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptor Expression and Susceptibility to Cholinergic Immunomodulation in Human Monocytes of Smoking Individuals

Abstract: <i>Objective:</i> Smoking is generally accepted as a factor that affects the disease course in inflammatory bowel disease patients. Whether these effects can be contributed to the immunomodulatory effects of nicotine via nicotinic acetylcholine receptor (nAChR) activation is unclear. As previous data suggest that the α7 nicotinic acetylcholine receptor <i>(CHRNA7)</i> and its duplicated variant <i>CHRFAM7A</i> may specifically participate in the inflammatory response of mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
3
19
0
Order By: Relevance
“…We and others have found that the α7 KO mouse has an enhanced pro-inflammatory response, demonstrated most often by an increase in TNFα release [13], [14], [34]. We find here that the α7 lin+ cells are those that are most responsive to stimulation with LPS and contribute substantially to the expression of certain cytokines (IL-12/23(p40)) while having little impact on the total expression of TNFα.…”
Section: Discussionsupporting
confidence: 56%
“…We and others have found that the α7 KO mouse has an enhanced pro-inflammatory response, demonstrated most often by an increase in TNFα release [13], [14], [34]. We find here that the α7 lin+ cells are those that are most responsive to stimulation with LPS and contribute substantially to the expression of certain cytokines (IL-12/23(p40)) while having little impact on the total expression of TNFα.…”
Section: Discussionsupporting
confidence: 56%
“…Very little is known regarding the regulation of CHRFAM7A gene expression, but at least 2 groups have reported that LPS inhibits both CHRNA7 and CHRFAM7A in undifferentiated human THP1 cells and human macrophages (31,32,43). In contrast, surprisingly little is published on the effects of LPS treatment in gut epithelial cells, presumably because these cells are constitutively exposed to LPS in vivo.…”
Section: Regulation Of Chrfam7a Expression In Intestinal Epithelial Cmentioning
confidence: 99%
“…In leukocyte cell lines like THP1 cells and in normal human monocytes, CHRFAM7A gene expression is reported to parallel that of CHRNA7 (31,32,43). Unfortunately, primer crosshybridization and antibody crossreactivities have confounded several studies that purport to measure CHRFAM7A gene expression or CHRFAM7A protein in cell lysates (31).…”
Section: Stdmentioning
confidence: 99%
“…For instance, the ratio of CHRNA7 : CHRFAM7A mRNA levels is different in bipolar subjects when compared to unaffected controls (De Luca et al 2006). Moreover, in vitro studies have demonstrated that two pro-inflammatory mediators characteristic of HIV-I infection, LPS and IL-1β, decrease CHRFAM7A expression leading to the suggestion that chronic pro-inflammatory responses might change the CHRFAM7A : CHRNA7 expression ratio (Benfante et al 2011; van der Zanden et al 2012). gp120 IIIB is unable to promote CHRNA7:CHRFAM7A alterations in the presence of AMD3100, an antagonist of CXCR4, suggesting that the gp120 IIIB -induced CHRNA7:CHRFAM7A dysregulation is CXCR4-dependent.…”
Section: Discussionmentioning
confidence: 99%